2012
DOI: 10.4149/neo_2013_014
|View full text |Cite
|
Sign up to set email alerts
|

Anisomycin Induces Apoptosis of Glucocorticoid Resistant Acute Lymphoblastic Leukemia CEM-C1 Cells via Activation of Mitogen-Activated Protein Kinases p38 and JNK

et al.

Abstract: Glucocorticoids (GCs) resistance is frequently encountered in children with acute lymphoblastic leukemia (ALL), especially in T-ALL, which usually results in failure of treatment. To find new agent to overcome GC resistance of ALL is an urgent problem. Here we investigated potential effect of anisomycin on GC-resistant T-ALL CEM-C1 cells and explored involved molecular mechanisms. Dramatic growth inhibition and apoptosis in GC resistant CEM-C1 cells and GC-sensitive CEM-C7 cells induced by anisomycin were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…6A). Upon increasing incubation times with anisomycin and sorbitol there was a progressive degradation of plectin, most likely reflecting proteolysis during apoptosis (Stegh et al, 2000) induced by these compounds (Marfe et al, 2009;Liu et al, 2013). In agreement with previous reports (Raingeaud et al, 1995;Kayali et al, 2000;Bagowski et al, 2003), we observed a rapid and long lasting stimulation of ERK1/2 in HeLa cells incubated with EGF, PMA and sorbitol, whereas anisomycin was a poor stimulator of ERK1/2.…”
Section: Recombinant Ps4642 Plectin Proteins Are Not Associated With supporting
confidence: 81%
“…6A). Upon increasing incubation times with anisomycin and sorbitol there was a progressive degradation of plectin, most likely reflecting proteolysis during apoptosis (Stegh et al, 2000) induced by these compounds (Marfe et al, 2009;Liu et al, 2013). In agreement with previous reports (Raingeaud et al, 1995;Kayali et al, 2000;Bagowski et al, 2003), we observed a rapid and long lasting stimulation of ERK1/2 in HeLa cells incubated with EGF, PMA and sorbitol, whereas anisomycin was a poor stimulator of ERK1/2.…”
Section: Recombinant Ps4642 Plectin Proteins Are Not Associated With supporting
confidence: 81%
“…Thus, JNK inhibition, or a key downstream JNK target, may allow GC sensitization in both B‐ and T‐lineage ALL . Our data adds to the increasing evidence that MAPK pathways modulate GC response in ALL cells and, more recently, anisomycin, a protein synthesis inhibitor and p38 (also termed MAPK14) agonist, was shown to resensitize GC response via activation of both p38 and JNK (Miller et al , ; Garza et al , ; Liu et al , ).…”
Section: Discussionsupporting
confidence: 62%
“…36 Furthermore, p38 pathway-mediated apoptosis was also observed in different cell types. 37, 38 In addition, Erk activation is essential for carcinogenesis, 39 and constitutively activated Erk is found in a variety of human cancers. 40 …”
Section: Discussionmentioning
confidence: 99%